Collective effects in multi-field inflation - Hassan, Sultan (Department of Mathematics and Applied Mathematics, 2014)
We present a new model of multi-field inflation in the limit when, N, the number of fields is very large. To implement this limit, we reformulate the problem in terms of a colourless bilocal field [(x; y) which encodes the collective degrees of freedom of the N scalar fields. As a concrete example, we apply the collective field theory formalism to the bosonic O(N) vector model with quartic self interaction minimally coupled to gravity and show how this may be used to model the quantum to classical transition out of inflation.